2015
DOI: 10.28930/jitkt.v7i1.9772
|View full text |Cite
|
Sign up to set email alerts
|

EXTRACTION AND CHARACTERIZATION OF FUNCTIONAL PROPERTIES OF CARRAGEENAN Kappaphycus alvarezii FROM COAST OF KUTAI TIMUR DISTRICT

Abstract: <p><em>Carrageenan is a gelling form of polysaccharide obtained from extraction process of red seaweeds (<span style="text-decoration: underline;">Rhodophyceae</span>) including <span style="text-decoration: underline;">Kappaphycus</span> <span style="text-decoration: underline;">alvarezii</span>. Carrageenan is widely used for pharmacy, cosmetics,  food,  gelling,  and  binding  agent  as  well  as  emulsifier  and  stabi-lizer. The quality of carrageenan is aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Dried seaweed was washed with tap water to remove salt and other compounds. Extraction of carrageenan was done according to Asikin and Kusumaningrum [8] and Asikin et al [13]. Dried seaweed was weighed 40 g then soaked in the water for 3 h, subsequently rinsed and drained.…”
Section: Carrageenan Extractionmentioning
confidence: 99%
“…Dried seaweed was washed with tap water to remove salt and other compounds. Extraction of carrageenan was done according to Asikin and Kusumaningrum [8] and Asikin et al [13]. Dried seaweed was weighed 40 g then soaked in the water for 3 h, subsequently rinsed and drained.…”
Section: Carrageenan Extractionmentioning
confidence: 99%
“…This study found that the fiber content of the carrageenan was 0.65%. Other research like (Asikin et al, 2015) found higher number between 8-12%. Fiber content possesses strong correlation with viscosity.…”
Section: Characteristic Of Carrageenanmentioning
confidence: 71%
“…The sample was cooled for a while before put in desiccator for another 30 minutes, and weighed as weight (b). To calculate fiber content, we used the formula below (Asikin et al, 2015):…”
Section: Characteristic Of Carrageenanmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfate levels of carrageenan flour were analyzed using a method referring to FMC Corp [18]. According to Asikin et al [35], sulfate levels are important parameters in determining the quality of derivative products from seaweed polysaccharides. The value of the sulfate percentage produced by research carrageenans is fairly diverse.…”
Section: Sulfate Content Of Depolymerized Carrageenanmentioning
confidence: 99%